STUDENT’S DIFFICULTIES IN TRANSLATING IDIOMATIC EXPRESSION FROM ENGLISH INTO INDONESIAN LANGUAGE AT THE 5th SEMESTER DEPARTMENT OF ENGLISH EDUCATION AT UNPRI MEDAN - Pardede, Seniwati; Siburian, Desnawati Hotnauli; Nasution, Jamaluddin (ELT (English Language Teaching Prima Journal), 2022)
This study is about the difficulties in translating idiomatic expressions. The purpose of this research is to find out the students’ difficulties in translating idiomatic expressions from English into the Indonesian language, and the causes of the difficulties. The type of research method used in this study is the descriptive qualitative research method. Data from this study was collected and obtained through tests and questionnaires. The subject of this study was 10 students from the 5th semester in majoring English Education at UNPRI Medan. Tests were distributed to the students to find out the student’s ability to translate idiomatic expressions, and what their difficulties, the results of translation were totally inadequate on 17%, inadequate on 19%, adequate on 11%, almost completely successful on 11%, and successful on 42%. After that, the researchers found the students’ difficulties in translating idiomatic expressions were lexical difficulty at 15%, stylistic difficulty at 28%, cultural difficulty at 28%, and 29% for grammatical difficulty. Based on the questionnaires the researchers found several factors influenced students' difficulties in translating idioms, firstly their lack of knowledge of idiomatic expressions, secondly, lack of vocabulary mastery, and thirdly, the students also rarely practiced expression idioms in speaking and writing. As a result, it is suggested that students study books, articles, papers, song lyrics, and movie subtitles in English to broaden their knowledge of idioms. They should also practice using idioms in writing and everyday conversation. Keywords: difficulties, causes, translation, idiom